Key role of e g band broadening in nickel-based oxyhydroxides on coupled oxygen evolution mechanism - Haoyin Zhong; Qi Zhang; Junchen Yu; Xin Zhang; Chao Wu; Hang An; Yifan Ma; Hao Wang; Jun Zhang; Yong-Wei Zhang; Caozheng Diao; Zhi Gen Yu; et al. (Nature communications, 2023)
Abstract A coupled oxygen evolution mechanism (COM) during oxygen evolution reaction (OER) has been reported in nickel oxyhydroxides (NiOOH)-based materials by realizing e g * band (3d electron states with e g symmetry) broadening and light irradiation. However, the link between the e g * band broadening extent and COM-based OER activities remains unclear. Here, Ni1-xFexOOH (x = 0, 0.05, 0,2) are prepared to investigate the underlying mechanism governing COM-based activities. It is revealed that in low potential region, realizing stronger e g * band broadening could facilitate the *OH deprotonation. Meanwhile, in high potential region where the photon utilization is the rate-determining step, a stronger e g * band broadening would widen the non-overlapping region between d z 2 and a 1g * orbitals, thereby enhancing photon utilization efficiency. Consequently, a stronger e g * band broadening could effectuate more efficient OER activities. Moreover, we demonstrate the universality of this concept by extending it to reconstruction-derived X-NiOOH (X = NiS2, NiSe2, Ni4P5) with varying extent of e g * band broadening. Such an understanding of the COM would provide valuable guidance for the future development of highly efficient OER electrocatalysts.